CRISPR‐Enabled Tools for Engineering Microbial Genomes and Phenotypes. Issue 9 (12th July 2018) - Tarasava, Katia; Oh, Eun Joong; Eckert, Carrie A.; Gill, Ryan T.
Abstract : In recent years CRISPR‐Cas technologies have revolutionized microbial engineering approaches. Genome editing and non‐editing applications of various CRISPR‐Cas systems have expanded the throughput and scale of engineering efforts, as well as opened up new avenues for manipulating genomes of non‐model organisms. As we expand the range of organisms used for biotechnological applications, we need to develop better, more versatile tools for manipulation of these systems. Here the authors summarize the current advances in microbial gene editing using CRISPR‐Cas based tools and highlight state‐of‐the‐art methods for high‐throughput, efficient genome‐scale engineering in model organisms Escherichia coli and Saccharomyces cerevisiae . The authors also review non‐editing CRISPR‐Cas applications available for gene expression manipulation, epigenetic remodeling, RNA editing, labeling, and synthetic gene circuit design. Finally, the authors point out the areas of research that need further development in order to expand the range of applications and increase the utility of these new methods. Abstract : This review covers various applications of CRISPR‐based technologies in industrially relevant microorganisms. The authors provide an overview of different CRISPR‐Cas types and focus on the recent advances in gene editing and non‐editing applications, including gene silencing and activation, base editing, RNA targeting, and synthetic gene circuit design.